Enhancing the strength of sandy soil through enzyme-induced calcite precipitation - Muhammed, A. S. (Springer Science and Business Media Deutschland GmbH, 2021)
Enzyme-induced calcite precipitation (EICP) is a biocementation technique that has the potential to improve the engineering properties of sand. The effectiveness of the EICP treatment was evaluated based on the unconfined compressive strength (UCS) tests at various concentrations of cementation reagent (CCR) and curing periods. The treated sand was analysed for its calcium carbonate content and microstructural analysis using FESEM-EDX. The results showed an increase in unconfined compressive strength and calcium carbonate content at a higher concentration of cementation reagent. The UCS value and CaCO3 content of the treated samples are 161–552 kPa and 0.92–5.73%, respectively. There is a linear relationship between the UCS at various cementation reagent concentrations and the average calcium carbonate content.